Business Information Systems Workshops : BIS 2017 International Workshops, Poznań, Poland, June 28-30, 2017, Revised Papers /: BIS 2017 International Workshops, Poznań, Poland, June 28-30, 2017, Revised Papers. (2017) - Unknown
No abstract available